Factors Associated With Patient Experience From 2 Tertiary Care Hospitals—A Cross-Sectional Study From Karachi, Pakistan - Aqsa Amjad MBBS; Zaibun Nisa MBBS, FCPS; Sana Javed Khan MBBS; Sania Sabir Sethi BS; Asmara Ghafoor MBBS; Anoosha Iqbal MBBS; Farheen Shahzad MBBS; Mehmood Riaz MBBS, FCPS; Uzma Ghori MBBS, FCPS; Aysha Almas MBBs, FCPS, PhD (Journal of Patient Experience)
Healthcare systems are rapidly transitioning toward patient-centered models, however, there is limited data regarding this from low- and medium-income countries. This cross-sectional study included patients above 18 years, admitted to internal medicine services at 2 tertiary care hospitals in Karachi, Pakistan. The outcome was a patient experience, with independent factors including sociodemographic characteristics (age group, gender, education level, and financial status) and hospital stay-related factors (admission type, length of hospital stay, attending physician's academic designation, functional status, code status, number of consults, and number of surgical and radiological procedures). Among 499 patients, the mean (standard deviation) patient experience score was 44.1 (4.5). Multivariable regression analysis showed higher scores (>45) were associated with factors such as, >16 years of education (OR = 1.6, 95% CI, 0.7-3.9), higher physician academic rank (OR = 4.5, 95% CI, 2.0-9.8 for Associate Professors and OR 12.1, 95% CI, 6.6-22.1) more radiological investigations (OR = 1.3, 95% CI, 0.3-1.8) and undergoing surgical procedures (OR = 2.1, 95% CI, 0.8-5.8). Lower scores (<45) were associated with semiprivate ward admissions, patients with a functional level of II, and a higher number of consults. Overall, the study showed a good patient experience score. However, disparities exist, emphasizing the need for policies to improve patient awareness, physician training, and equitable care for all of those with functional limitations.